1998
DOI: 10.1038/sj.onc.1201587
|View full text |Cite
|
Sign up to set email alerts
|

Ursolic acid-induced down-regulation of MMP-9 gene is mediated through the nuclear translocation of glucocorticoid receptor in HT1080 human fibrosarcoma cells

Abstract: We have previously reported that ursolic acid, a pentacyclic triterpene acid, inhibited the invasion of HT1080 human ®brosarcoma cells by reducing the expression of matrix metalloproteinase-9. Since the chemical structure of ursolic acid is very similar to that of dexamethasone, a synthetic glucocorticoid, we investigated whether ursolic acid acts through the glucocorticoid receptor. The expression of matrix metalloproteinase-9 is thought to be regulated similarly with matrix metalloproteinase-1 and matrix met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 90 publications
(56 citation statements)
references
References 23 publications
3
53
0
Order By: Relevance
“…UA induces apoptosis through multiple pathways, such as inhibiting DNA replication (7,10); inducing Ca 2ϩ release (8); activating caspases (9,11); activating JNK (12); down-regulating antiapoptotic genes (13,14); inhibiting COX2 and iNOS (15,16); suppressing MMP-9 (17); and inhibiting protein tyrosine kinase (10), STAT3 (18), and NF-B activities (13). In animal studies, UA has been shown to be chemopreventive (19 -21), to suppress tumor invasion (17), and to inhibit experimental metastasis of esophageal carcinoma (22). Whether UA can modulate the effect of apoptosisinducing cytokines that are currently in clinical trial is not known.…”
mentioning
confidence: 99%
“…UA induces apoptosis through multiple pathways, such as inhibiting DNA replication (7,10); inducing Ca 2ϩ release (8); activating caspases (9,11); activating JNK (12); down-regulating antiapoptotic genes (13,14); inhibiting COX2 and iNOS (15,16); suppressing MMP-9 (17); and inhibiting protein tyrosine kinase (10), STAT3 (18), and NF-B activities (13). In animal studies, UA has been shown to be chemopreventive (19 -21), to suppress tumor invasion (17), and to inhibit experimental metastasis of esophageal carcinoma (22). Whether UA can modulate the effect of apoptosisinducing cytokines that are currently in clinical trial is not known.…”
mentioning
confidence: 99%
“…In breast cancer patients, TFAP2A is highly associated with MMP9 expression (Pellikainen et al, 2004). NRC3C1 is a nuclear receptor that can inhibit expression of MMP9 (Cha et al, 1988). In conjunction with elevated levels of HMGA1 and TFAP2, reduced expression of this gene may lead to increased MMP9 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the concrete mechanisms of its anticancer effects are poorly understood, several studies have found that UA can inhibit proliferation and induce apoptosis of many tumor cell lines. 2 UA-induced apoptosis occurs through multiple pathways such as the inhibition of DNA replication, 3 induction of Ca 2+ release, 4 activation of caspases 5,6 and c-Jun N-terminal kinase, 7,8 phosphorylation of glycogen synthase kinase 3-β, downregulation of antiapoptotic genes, 9 inhibition of cyclooxygenase-2 and inducible nitric oxide synthase, 10,11 suppression of matrixmetallopeptidase-9, 12 and the inhibition of protein tyrosine kinase, 13 phosphatidylinositol-3-kinase, 14 single transducer and activator of transcription 3, 15 adenosine 5′-monophosphate-activated protein kinase, 16 and nuclear factor κ-light-chain-enhancer of activated B cells 17 pathways. Furthermore, UA can inhibit the differentiation, angiogenesis, invasion, and metastasis of tumor cells as well as interfere with numerous enzymes such as those directly involved with DNA synthesis and repair.…”
Section: Introductionmentioning
confidence: 99%